Estimation of Plunge Value in Single- or Multi-Layered Anisotropic Media Using Analysis of Fast Polarization Direction of Shear Waves - K. Latifi; A. Sadidkhouy; M. R. Ghassemi (Journal of Sciences, Islamic Republic of Iran)
Estimation of the fast polarization direction of shear seismic waves that deviate from horizontal axis is a valuable approach to investigate the characteristics of the lower crust and uppermost mantle structures. The lattice preferred orientation of crystals, which is generally parallel to the downward or upward flow of the mantle or crust, is an important reason for the occurrence of fast axis plunge in these structures. We introduce a new method to estimate the plunge and the true percent of anisotropy. To evaluate the accuracy of the method, we applied it to back azimuthal synthetic receiver functions produced by the Raysum code. The output resulted from this new method (including plunge and percent of anisotropy) were compared with inputs of Raysum code, and reveal that there is a very good coherence among the inputs and output values estimated by our method. This method has been applied to anisotropy analysis beneath two different stations of SHGR in Iran and MOX in Germany. The splitting parameters beneath the SHGR station, are estimated to be φ=60±1 degrees and δt=0.54±0.02 sec. The plunge value and percentage of anisotropy in SHGR are estimated to be 45±0.5 degrees and 4 percent, which can correspond to an old flow in a subduction zone within the area. The splitting parameters in the crust beneath the MOX station, are estimated as φ=98±2 degrees and δt=0.38±0.02 sec. The plunge value and percentage of anisotropy in the crust of the MOX are estimated 45±0.2 degrees and 5.5%.